MAPPING PERCEPTION OF CONSUMER ANTIVIRUS SOFTWARE WITH MULTIDIMENSIONAL SCALING METHOD - Nurhayati, Ai; ., Frencius (APTIKOM Publisher, 2019)
Antivirus software industry is growing rapidly in the world in 2018. The domestic antivirus software industrymust be able to compete on a global scale. To face free trade, Indonesia's antivirus software industry must be able toknow its position in the minds of consumers, especially domestic consumers. In this research, Smadav will representthe antivirus software industry from Indonesia. In this research want to know how the position of smadav comparedwith its current competitors, namely Avast, Avira, AVG, Kaspersky, McAfee and Norton. This research is only done tomap antivirus software based on similarity according to respondent's perception. This research uses Multidimensionalscaling (MDS) method through SPSS software program version 23. The results showed that there are three groups ofdifferent antivirus software based on similarity level according to the respondent's perception. On the two-dimensionaland three-dimensional maps Norton antivirus software, Avast and Avira have similar resemblance according to therespondent's perception, because the location is closest and is in the same quadrant. Smadav differs according toperceptions of respondents. AVG, McAfee and Kaspersky have similarities according to respondents' perceptions.